Age models for ten Iberian Margin sediment cores during the last glacial cycle (0-150 ka BP) - Lorraine E Lisiecki; Alan M Jones; Devin S Rand; Charles E Lawrence (PANGAEA, 2021)
Interpretations of paleoclimate records from ocean sediment cores rely on age models to provide estimates of age as a function of core depth. As one metric of age model uncertainty, we compare four dating methods using high-resolution data over the last glacial cycle from ten Iberian Margin cores. The first method uses radiocarbon data and the Bayesian statistical software Bacon [Blaauw and Christen, 2011] . The second method aligns benthic δ18O to a target core using the probabilistic alignment algorithm HMM-Match [Lin et al., 2014] . The third and fourth methods are alignment of planktonic δ18O and sea surface temperature (SST), respectively, using the deterministic alignment software Match [Lisiecki and Lisiecki, 2002] . Where three or more age model types overlap in a core, the average range of age estimates is 1.7 kyr, and 90% of age ranges are less than 3 kyr. For the two probabilistic methods, HMM-Match and Bacon, age estimates agree to within uncertainty, and the highest resolution records yield 95% confidence interval widths of 1-2 kyr. However, HMM-Match appears to underestimate alignment uncertainty near benthic δ18O gaps in one core, as indicated by disagreement with the core extquotesingles planktonic δ18O and SST alignments. Because planktonic δ18O and SST proxies appear to provide reliable alignments on the Iberian Margin, probabilistic alignment algorithms should be developed for these proxies. Ultimately, the most reliable age models would incorporate information from as many proxies as possible.